Evaluation of the Gerakan Nasional Revolusi Mental (GNRM) Policy in Improving Tolerance and Harmony among Religious Communities - Mukhammad Fahrurozi; Fernandes Simangunsong; Muhadam Labolo; Layla Kurniawati (Smart Society, 2026)
The Gerakan Nasional Revolusi Mental (GNRM) [National Mental Revolution Movement] aims to strengthen Pancasila values however, its implementation in multicultural Jakarta continues to face challenges related to value consistency, interagency coordination, and public participation. This study aims to evaluate the implementation of the GNRM policy in improving tolerance and harmony among religious communities, identify supporting and inhibiting factors, and formulate reflective strategies to strengthen value-based governance in Jakarta, Indonesia. The study uses a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model. The data was collected through in-depth interviews, field observations, and document analysis involving 25 informants, including policymakers, religious leaders, and civil society organizations. The analysis was conducted through open, axial, and selective coding to establish thematic relationships between empirical findings and conceptual reflections. The main findings show that: (1) GNRM contributes positively to strengthening social tolerance, discipline, and cooperation among citizens; (2) there are still limitations in bureaucratic synchronization and reflective monitoring mechanisms; and (3) local leadership commitment and interfaith collaboration are key supporting factors. This study introduces the concept of Value-Based Policy Evaluation, which integrates moral, social, and bureaucratic dimensions into public policy analysis. Overall, the results confirm that value-based governance can bridge bureaucratic systems and social culture to achieve sustainable policy outcomes. The policy implications emphasize the need to institutionalize Pancasila values through an adaptive and learning-oriented governance framework at the central and regional levels.